Lateral extrusion along the Altyn Tagh Fault, Qilian Shan (NE Tibet): insight from a 3D crustal budget. (17th September 2015) - Cheng, Feng; Jolivet, Marc; Dupont‐Nivet, Guillaume; Wang, Lin; Yu, Xiangjiang; Guo, Zhaojie
Abstract: The lithospheric strike‐slip Altyn Tagh Fault has accommodated hundreds of kilometres of displacement between the Qaidam and Tarim blocks since its Eocene reactivation. However, the way the deformation is accommodated in the Qilian Shan and further east remains uncertain. Based on 360 km of north‐eastward migration of the relatively rigid Qaidam block along the Altyn Tagh Fault and 3D isovolumetric balancing of the crustal deformation within the Altyn Tagh Fault–Qilian Shan system, we demonstrate that 250 ± 28 km (43.8–49.4%) of N20E directed crustal shortening and an additional 250–370 km of eastward motion of the Qilian Shan crust must be accounted for by strike‐slip faulting in the Qilian Shan and crustal thickening in the Qinling area, as well as by extension in the adjoining North China block graben systems.